Design and study of ultra-wideband folded loop antennas - LV Wen-jun; ZHU Hong-bo (Tongxin xuebao)
Design of a novel ultra-wideband folded loop antenna was proposed.It was fed by coplanar waveguide and can be easily integrated with other microwave circuits.By introducing a pentagonal folded loop,the bandwidth of the an-tenna is improved twice than that of conventional folded loop antenna.Parametric study is carried out numerically by us-ing EM simulators.Based on numerical results,the antenna is also studied experimentally.As can be seen,an operation bandwidth of over 4.75:1 is obtained.The presented antenna may be practical for ultra-wideband applications.